EVALUATION OF BLACK TEA BIOACTIVE COMPOUNDS USING IN SILICO AND IN VITRO METHODS AS ACETYLCHOLINESTERASE INHIBITOR - NUR AZIZAH , ROSI
Alzheimer's (AD) is a neurodegenerative disease characterized by progressive failure of thinking, lost of memory and language. AD is more specifically characterized by the formation of neuritic plaque accumulations of ?-amyloid peptide (A?) and neurofibrillary tangles (NFT) caused by hyperphosphorylation tau protein. AD often attacks the elderly. Percentage of AD sufferers every year has increased. Problems associated with AD are very complex, including expensive to treat, etiology is unclear and available treatments have side effects to patient. Types of AD treatment approved by FDA are N-methyl-D-aspartate (NMDA) such as memantine and acetylcholinesterase inhibitors such as donepezil, rivastagmine and galantamine.